2010
DOI: 10.1007/s12613-010-0102-5
|View full text |Cite
|
Sign up to set email alerts
|

Ore-proportioning optimization technique with high proportion of Yandi ore in sintering

Abstract: The basic sintering characteristics of Yandi ore from Australia, including assimilation ability, liquid phase fluidity, self-strength of bonding phase, forming ability of silico ferrite of calcium and aluminum (SFCA), and so on, were investigated in detail. Besides, the high temperature behavior and function of sintering were obtained. As a result, the techniques for ore-proportioning in sintering were obtained. The results show that Yandi ore possessing higher assimilation ability, better liquid phase fluidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…In addition to the traditional room temperature characteristics of iron ores, high temperature characteristics of iron ores get the attention of researchers gradually. WU's research indicated that 5 kinds of high temperature characteristics of iron ores could reflect the behavior and role of iron ores in the sintering process, 1) and differences of assimilation characteristics between various iron ores and the ore blending optimization based on the high temperature characteristics such as assimilation characteristic has been also studied, 2,3) but the influencing factors of the assimilation characteristic of iron ores were not studied clearly. In addition, Yang 4) also studied the reaction between nuclei iron ores with the initial melt formed in the adhesive powder, and the assimilation was evaluated by the composition of the mineral composition, which was different from the assimilation temperature of iron ores in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the traditional room temperature characteristics of iron ores, high temperature characteristics of iron ores get the attention of researchers gradually. WU's research indicated that 5 kinds of high temperature characteristics of iron ores could reflect the behavior and role of iron ores in the sintering process, 1) and differences of assimilation characteristics between various iron ores and the ore blending optimization based on the high temperature characteristics such as assimilation characteristic has been also studied, 2,3) but the influencing factors of the assimilation characteristic of iron ores were not studied clearly. In addition, Yang 4) also studied the reaction between nuclei iron ores with the initial melt formed in the adhesive powder, and the assimilation was evaluated by the composition of the mineral composition, which was different from the assimilation temperature of iron ores in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…SJY was a fine ore with 96.31% passing 0.2 mm, 100% passing 1 mm, however YD was coarse ore with only 8.37% passing 0.2 mm, 29.91% passing 1 mm. The experimental method of sintering basic characteristics had been introduced in relevant literature; the paper will not repeat the description [12][13][14].…”
Section: Characterizationmentioning
confidence: 99%
“…The sinter basic characteristic of different ore (a: assimilability temperature; b: liquidity index; c: bonding phase strength)The effect of SiO2 content on the assimilability temperature is shown inFig 4.The SiO2 content had a quadratic relationship with the assimilation temperature as shown in Eq (13)…”
mentioning
confidence: 99%
“…Therefore, the self-strength of the bonding phase played an important role in the strength of the sinter [15,[20][21]. The blending ore and flux were mixed according to a certain binary basicity, and then extruded into a cylindrical cake sample.…”
Section: (3) Consolidation Strengthmentioning
confidence: 99%